Aplikasi Panduan Ibadah Haji Berbasis Android - Deddy Sucipta Syahril; R. Rizal Isnanto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
This is an application for hajj guidance based on Android.The application is made using software Eclipse IDE and Android SDK with Java as a programming language. Stage of development software used is SDLC (Software Development Life Cycle) by using the method waterfall, as modeling software used is UML (Unified Modelling Language). Steps in this research are software requirement analysis, design, coding, and system testing. Functional testing using a method of black box.The result of this research is an application of hajj guidance based on Android can be use to guide in hajj. The application can run well on a device with a minimum of Android operating system version 4.2 (Jelly Bean) with the storage space available at least 25 MB. Function menus and buttons is operated appropriately according to their functions. This application for hajj guidance can be used as a medium to help moslems in hajj.